2021
DOI: 10.21203/rs.3.rs-939475/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of malnutrition in School aged children, Kassala State, Sudan

Abstract: Background : Childhood malnutrition is a major concern in developing countries due to high morbidity and mortality rate. To estimate the prevalence of malnutrition among school children, Kassala State, A cross-sectional study was conducted randomly among 2638 children. Height for age and body mass index for age z scores were calculated using WHO Anthro Plus software as indicators of stunting and thinness respectively. A multinomial logistic regression model was used to determine the associated factors. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
0
1
Order By: Relevance
“…Nearly same prevalence of wasting/thinness was observed in Ghana (prevalence was 19.4% among 650 school children) (16), Sri Lanka (prevalence was 20.9% among 4484 school students aged 5-10 years) (19) and Sudan (prevalence was 23.1% among 835 primary school children aged 6-14 years) (24). Contrary to this study, increased prevalence of wasting/thinness was reported from India (prevalence was 33.3% among urban school age children) (22), Sudan (prevalence was 32.3% among 2638 school children aged 5-15 years) (17), and Democratic Republic of Congo (prevalence was 29.7% among 197 primary school children aged 7-17 years) (4),. Lower prevalence of wasting/thinness than this study were observed in Pakistan (prevalence was 10.1% among 1860 urban primary school children aged 5-12 years) (23), Ethiopia (prevalence was 9.8% among 396 urban primary school children aged 5-12 years) (25), Kenya (prevalence was 4.5% among 384 school children aged 6-12 years living in a low-income urban community) (20), and India (prevalence was 2.0% among 100 rural school children aged 6-14 years) (18).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Nearly same prevalence of wasting/thinness was observed in Ghana (prevalence was 19.4% among 650 school children) (16), Sri Lanka (prevalence was 20.9% among 4484 school students aged 5-10 years) (19) and Sudan (prevalence was 23.1% among 835 primary school children aged 6-14 years) (24). Contrary to this study, increased prevalence of wasting/thinness was reported from India (prevalence was 33.3% among urban school age children) (22), Sudan (prevalence was 32.3% among 2638 school children aged 5-15 years) (17), and Democratic Republic of Congo (prevalence was 29.7% among 197 primary school children aged 7-17 years) (4),. Lower prevalence of wasting/thinness than this study were observed in Pakistan (prevalence was 10.1% among 1860 urban primary school children aged 5-12 years) (23), Ethiopia (prevalence was 9.8% among 396 urban primary school children aged 5-12 years) (25), Kenya (prevalence was 4.5% among 384 school children aged 6-12 years living in a low-income urban community) (20), and India (prevalence was 2.0% among 100 rural school children aged 6-14 years) (18).…”
Section: Discussioncontrasting
confidence: 88%
“…Compared to this study, higher prevalence of stunting has been reported from Democratic Republic of Congo (prevalence was 61.0% among 197 primary school children aged 7-17 years) (4), Ethiopia (prevalence was 57% among 633 rural community 6-12 years old school age children) (15), and Ghana (prevalence was 50.3% among 650 school children) (16). However, lower prevalence of stunting has been reported from Sudan (prevalence was 22.1% among 2638 school children aged 5-15 years) (17), India (prevalence was 36.0% among 100 rural school children aged 6-14 years) (18), Sri Lanka (prevalence was 30.3% among 4484 school students aged 5-10 years) (19), Kenya (prevalence was 30.2% among 384 school children aged 6-12 years living in a low-income urban community) (20), China (prevalence was 11.7% among 1474 rural school children aged 5-12 years) (21), India (prevalence was 18.5% among urban school age children) (22), Pakistan (prevalence was 8.2% among 1860 urban primary school children aged 5-12 years) (23) and Sudan (prevalence was 7.1% among 835 primary school children aged 6-14 years) (24). These differences of prevalence observed during different countries (or different areas of the same country) could be due to differences in sample size, socioeconomic status, living condition, health policy, child feeding practices, school feeding programs, and child health care.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is comparable with other studies conducted in Arba Minch 8.0%, 12 Gondar town northwest Ethiopia 9%, 6 South Gondar Zone, Ethiopia-6.3% 17 and Kallin District, Kafr El-Sheikh Governorate, Egypt 6.7%. 28 However, the finding of this study was lower than those of studies done in Mecha woreda, Amhara regional state, Ethiopia 10.8%, 23 Fogera and Libo Kemkem districts, northwest Ethiopia 21.4%, 7 Ethiopia 18.2%, 24 Dembia district, North West Ethiopia 13% 25 Nsukka, Nigeria 13.0%, 21 Kassala State, Sudan 32.3% 32 and Rural Madagascar 11.2%. 33 The possible reason for this might be seasonal variation and the variability of risk factors across different geographic settings.…”
Section: Discussioncontrasting
confidence: 71%